A uniform silicone rubber / epoxy glass fiber interface electric field adhesive and preparation method thereof

By using silane coupling agent to graft P-type AgAlO2 nanoparticle material as adhesive on the silicone rubber/epoxy glass fiber interface of composite insulators, the problems of interfacial electric field distortion and aging are solved, and the uniform electric field distribution and aging resistance of the interface are improved.

CN116355582BActive Publication Date: 2025-04-18GUANGDONG POWER GRID CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310360349.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2025-04-18
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

There is electric field distortion and partial discharge of the silicone rubber/epoxy glass fiber interface in the composite insulator, resulting in material aging and failure, and the existing interface adhesive cannot effectively uniformize the interface electric field.

Method used

The P-type AgAlO2 nanoparticle material is grafted as the adhesive by using a silane coupling agent to homogenize the electric field of the silicone rubber/epoxy glass fiber interface by forming hydrogen bonds and covalent bonds at the interface.

Benefits of technology

It effectively reduces the strength of the interface distortion electric field, improves the interface's electric field aging resistance, reduces the interface failure rate of the insulator, and ensures the normal operation of the insulator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116355582B_ABST
    Figure CN116355582B_ABST
Patent Text Reader

Abstract

The present invention discloses an adhesive for uniform silicone rubber / epoxy glass fiber interface electric field and a preparation method thereof. The adhesive for uniform silicone rubber / epoxy glass fiber interface electric field of the present invention is a silane coupling agent grafted with a P-type AgAlO2 nanoparticle material; the silane coupling agent is a vinyl silane coupling agent and / or a methacrylate silane coupling agent; the P-type AgAlO2 nanoparticle is obtained by surface-modifying micron-sized Al(NO3)3·9H2O with AgNO3. When defects such as air gaps exist at the silicone rubber / epoxy glass fiber interface, the adhesive of the present invention plays a role in uniform electric field to reduce the maximum value of the polarization electric field to which the silicone rubber and epoxy glass fiber are subjected, thereby reducing the hazards such as heat generation and power generation caused by interface defects, improving the electric field aging resistance of the interface, reducing the interface failure rate of the insulator, and ensuring the normal operation of the insulator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulating adhesive materials, and in particular to an adhesive for uniform silicone rubber / epoxy glass fiber interface electric field and a preparation method thereof. Background Art

[0002] Composite insulators have good electromechanical properties, but they will experience high electric fields and harsh environmental conditions in outdoor operating environments. With the increase of operating years, composite insulators generally show appearance aging problems such as decreased hydrophobicity, discoloration, hardening, brittleness, and powdering of the shed. Compared with the appearance aging problem, more attention is paid to the internal interface failure and fault of the composite insulator during operation. As the weak link of the composite insulator, the silicone rubber / epoxy fiberglass interface has a more hidden failure problem. The air gap, moisture and defects at the silicone rubber / epoxy fiberglass interface can cause electric field distortion and partial discharge inside the insulator, causing material aging and ultimately leading to moisture intrusion. This not only affects the electrical and mechanical properties of the composite insulator, but also significantly accelerates the aging and even fracture of the core rod. The simulation results show that moisture or air gap defects at the high-voltage end of the insulator core rod will cause uneven electric field distribution in the adjacent 15mm to 20mm length range, resulting in obvious distortion, which is a hidden danger of silicone rubber / epoxy fiberglass interface breakdown. The uneven distribution of electric field is a common problem in high-voltage power insulation equipment and components, which brings great technical difficulties and excessive costs to the design and manufacture of high-voltage and ultra-high-voltage equipment, and endangers the safety and reliability of long-term operation of equipment. Therefore, it is necessary to improve the uniformity of the electric field at the silicone rubber / epoxy fiberglass interface of the insulator.

[0003] At present, the interface adhesive used in the industrial production of composite insulators is mainly a small molecule silane coupling agent, which is used to form a strong interface bond between the sheath and the core rod to reduce the interface leakage current. However, when there are defects at the silicone rubber / epoxy fiberglass interface, the interface electric field cannot be uniform, reducing the invisible electric field aging of the insulator. Summary of the invention

[0004] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide an adhesive with a uniform silicone rubber / epoxy glass fiber interface electric field and a preparation method thereof.

[0005] The purpose of the present invention is achieved through the following technical scheme: an adhesive for uniform silicone rubber / epoxy glass fiber interface electric field is a silane coupling agent grafted P-type AgAlO2 nanoparticle material.

[0006] The silane coupling agent is a vinyl silane coupling agent and / or a methacrylate silane coupling agent.

[0007] The P-type AgAlO2 nanoparticles are obtained by surface-modifying micron-sized Al(NO3)3·9H2O with AgNO3.

[0008] The preparation method of the above-mentioned adhesive with uniform silicone rubber / epoxy glass fiber interface electric field comprises the following steps:

[0009] (1) Dissolve aluminum in nitric acid, boil, remove impurities, evaporate and concentrate, cool, filter, wash and dry the precipitated crystals to obtain Al(NO3)3·9H2O;

[0010] (2) dissolving the Al(NO3)3·9H2O and AgNO3 in water, adjusting the pH value of the solution to 13-14 with alkali, stirring, reacting, washing the obtained precipitate with ammonia water and nitric acid in turn until the pH value of the solution reaches neutral, rinsing with water, and drying to obtain P-type AgAlO2 nanoparticles;

[0011] (3) mixing ethanol solution, isopropanol, methanol, acetic acid and concentrated nitric acid to obtain an adhesive solvent having a pH value of 4.5 to 3.5;

[0012] (4) Dispersing the P-type AgAlO2 nanoparticles, vinyl silane coupling agent and / or methacrylate silane coupling agent in an adhesive solvent in sequence, washing, filtering, and drying to obtain an adhesive.

[0013] Preferably, the concentration of nitric acid in step (1) is 20-80% by volume.

[0014] Preferably, the temperature of the evaporation concentration in step (1) does not exceed 75°C.

[0015] Preferably, the crystal filtration in step (1) uses filter paper with a pore size of 30 to 50 μm.

[0016] Preferably, the washing in step (1) is performed using 0°C ice water.

[0017] Preferably, the molar ratio of Al(NO3)3·9H2O to AgNO3 in step (2) is 1:1-1.2.

[0018] Preferably, the base in step (2) is NaOH.

[0019] Preferably, the stirring time in step (2) is 1-8 hours.

[0020] Preferably, the reaction in step (2) is carried out at 150-250° C. for 20-80 h.

[0021] Preferably, the concentration of the ammonia water in step (2) is 0.5-3 mol / L.

[0022] Preferably, the concentration of nitric acid in step (2) is 0.1-2 mol / L.

[0023] Preferably, the water used in the ethanol solution in step (3) is pure water with a conductivity of less than 2uS / cm.

[0024] Preferably, the concentration of the ethanol solution in step (3) is 78% by volume; the volume ratio of the ethanol solution, isopropanol, methanol, acetic acid and concentrated nitric acid is 100 mL: 4-6: 4-6: 4-6: 4-6.

[0025] Preferably, the amount of the P-type AgAlO2 nanoparticles, vinyl silane coupling agent and / or methacrylate silane coupling agent in step (4) is calculated according to the ratio of 1g of P-type AgAlO2 nanoparticles to 10-15ml of vinyl silane coupling agent and / or methacrylate silane coupling agent.

[0026] Preferably, the P-type AgAlO2 nanoparticles in step (4) are dispersed by stirring in a water bath at 40-60°C for 10-15 min, followed by ultrasonic treatment at a power of 60-120w for 10-15 min.

[0027] Preferably, the vinyl silane coupling agent and / or methacrylate silane coupling agent in step (4) is dispersed by stirring in a water bath at 30-80° C. for 5-10 min.

[0028] The p-type AgAlO2 nanoparticles of the present invention are obtained by modifying the surface of homemade micron-sized Al(NO3)3·9H2O with nitric acid, and the interfacial compatibility between AgAlO2 and conventional silane coupling agents is improved by increasing the hydroxyl groups on the surface of the AgAlO2 material. The vinyl silane coupling agent and / or the methacrylate silane coupling agent can undergo hydrolysis reaction with an ethanol solution under acidic conditions to generate hydroxyl groups. The hydroxyl groups generated by the hydrolysis of the silane coupling agent and the hydroxyl groups on the surface of the p-type AgAlO2 nanoparticles form hydrogen bonds, which are then dehydrated and condensed to form covalent bonds, and the coupling agent molecules are grafted onto the surface of the p-type AgAlO2 nanoparticles to obtain an adhesive with a uniform silicone rubber / epoxy glass fiber interface electric field.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The interface adhesive of the present invention is obtained by compounding a P-type AgAlO2 nanomaterial with a vinyl silane coupling agent and / or a methacrylate-based silane coupling agent. The P-type AgAlO2 nanoparticles of the present invention have good chemical stability. When there are defects such as air gaps at the silicone rubber / epoxy glass fiber interface, the accompanying distorted electric field will destroy the balance of free holes in the P-type AgAlO2 nanoparticles, and the free holes will shift in the direction of the electric field lines. Since the electric field generated by the space charge offsets the external electric field, the distorted electric field intensity in the gap will be weakened, playing the role of a uniform electric field. The adhesive of the present invention for uniform silicone rubber / epoxy glass fiber interface electric field can make the distorted electric field at the silicone rubber / epoxy glass fiber interface uniform, so as to reduce the maximum value of the polarization electric field on the silicone rubber and epoxy glass fiber, thereby reducing the hazards such as heat generation and power generation caused by interface defects, improving the performance of the interface's resistance to electric field aging, reducing the insulator interface failure rate, and ensuring the normal operation of the insulator. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the test result of the electric field strength at the interface of silicone rubber / epoxy glass fiber of composite insulator.

[0032] Figure 2 This is the result of the heat generation test on the interface defect of silicone rubber / epoxy glass fiber of composite insulator. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example

[0035] (1) Preparation of Al(NO3)3·9H2O: Under heating conditions, 1 mol of aluminum was dissolved in nitric acid with a concentration of 60%, filtered to remove impurities after boiling, evaporated and concentrated at 70°C, cooled to room temperature, crystals were precipitated, and filtered with filter paper with a pore size of 40 μm to obtain crystals. The crystals were washed three times with 0°C ice water and placed in a sulfuric acid dryer for a short time to obtain Al(NO3)3·9H2O.

[0036] (2) Prepare the reactant solution: Dissolve 150 mmol Al(NO3)3·9H2O and 150 mmol AgNO3 in 700 mL deionized water to obtain a clear solution at room temperature.

[0037] (3) 0.6 mol NaOH was added to the solution to adjust the pH value of the solution to 14, and the solution was stirred for 3 h to obtain a suspension, which was poured into a 1000 mL Teflon-lined autoclave. The autoclave was sealed and maintained at 200° C. for 60 h to obtain a precipitate.

[0038] (4) The obtained precipitate was washed with diluted ammonia (1 mol / L) and diluted nitric acid (1 mol / L) in sequence until the pH value of the solution reached neutral. Finally, the precipitate was rinsed with deionized water several times and dried to obtain p-type AgAlO2 nanoparticles.

[0039] (5) Preparation of adhesive solvent: Anhydrous ethanol and pure water (conductivity of 1.8 uS / cm) were prepared into 100 mL of ethanol solution in a volume ratio of 78:22, 5 mL of isopropanol and 5 mL of methanol were added to the ethanol solution, and 5 mL of anhydrous acetic acid and 5 mL of concentrated nitric acid were slowly added dropwise until the pH value of the solution reached 4, thereby obtaining an adhesive solvent.

[0040] (6) Add 1g of p-type AgAlO2 nanoparticles to the adhesive solvent, stir for 15 minutes in a 40°C water bath, and then ultrasonically treat for 15 minutes at a power of 90W. After ultrasonic dispersion, add 12ml of vinyl silane coupling agent and stir for 8 minutes in a 40°C water bath. Wash and filter the product several times, and vacuum dry it to constant weight to obtain a silane coupling agent grafted p-type AgAlO2 nanoparticle material, that is, an adhesive with a uniform silicone rubber / epoxy glass fiber interface electric field.

[0041] Comparative Example 1

[0042] (1) Preparation of Al(NO3)3·9H2O: Under heating conditions, 1 mol of aluminum was dissolved in nitric acid with a concentration of 60%, filtered to remove impurities after boiling, evaporated and concentrated at 70°C, cooled to room temperature, crystals were precipitated, and filtered with filter paper with a pore size of 40 μm to obtain crystals. The crystals were washed three times with 0°C ice water and placed in a sulfuric acid dryer for a short time to obtain Al(NO3)3·9H2O.

[0043] (2) Preparation of adhesive solvent: Anhydrous ethanol and pure water (conductivity of 1.8 uS / cm) are prepared into 100 mL of ethanol solution in a volume ratio of 78:22, 5 mL of isopropanol and 5 mL of methanol are added to the ethanol solution, and 5 mL of anhydrous acetic acid and 5 mL of concentrated nitric acid are slowly added dropwise until the pH value of the solution reaches 4, thereby obtaining an adhesive solvent.

[0044] (3) Add 1g of p-type AgAlO2 nanoparticles to the adhesive solvent, stir for 15min in a 40℃ water bath, and then ultrasonically treat for 15min at a power of 90W. After ultrasonic dispersion, add 12ml of vinyl silane coupling agent and stir for 8min in a 40℃ water bath. Wash and filter the product several times, and vacuum dry it to constant weight to obtain silane coupling agent grafted AgAlO2, i.e., an adhesive with uniform silicone rubber / epoxy glass fiber interface electric field.

[0045] Comparative Example 2

[0046] (1) Preparation of adhesive solvent: Anhydrous ethanol and pure water (conductivity of 1.8 uS / cm) are prepared into 100 mL of ethanol solution in a volume ratio of 78:22, 5 mL of isopropanol and 5 mL of methanol are added to the ethanol solution, and 5 mL of anhydrous acetic acid and 5 mL of concentrated nitric acid are slowly added dropwise until the pH value of the solution reaches 4, thereby obtaining an adhesive solvent.

[0047] (2) Add 1g of AgAlO2 to the adhesive solvent, stir for 15 minutes in a water bath at 40°C, and then ultrasonically treat for 15 minutes at a power of 90W. After ultrasonic dispersion, add 12ml of vinyl silane coupling agent and stir for 8 minutes in a water bath at 40°C. Wash and filter the product several times, and vacuum dry it to constant weight to obtain silane coupling agent grafted AgAlO2, that is, an adhesive with uniform silicone rubber / epoxy glass fiber interface electric field.

[0048] test

[0049] Interface electric field strength test: In order to study the influence of the adhesives of Example 1 and Comparative Examples 1 and 2 on the electric field distribution of the silicone rubber / epoxy glass fiber interface of the composite insulator, the electric field strength of the interface of the 220kV insulator to which the three kinds of adhesives were added was simulated. The results are as follows: Figure 1 and Table 1. The test results show that the adhesive of Example 1 has a good uniform effect on the electric field of the silicone rubber / epoxy glass fiber interface of the composite insulator.

[0050] Table 1 Maximum value of electric field strength

[0051] Performance Testing Example Comparative Example 1 Comparative Example 2 Maximum field strength (kV / cm) 4.3 7.3 16.8

[0052] Defect heating test: The temperature at the interface defect of the composite insulator silicone rubber / epoxy glass fiber using the adhesive of Example 1 and Comparative Example 2 was tested using an insulator heating detection device. The results are as follows: Figure 2 The more severe the heat generated at the interface defect, the greater the electric field distortion. The test results show that the adhesive obtained by grafting P-type AgAlO2 nanoparticles with silane coupling agent can reduce the heat caused by interface defects, thereby improving the interface's resistance to electric field aging, reducing the insulator interface failure rate, and ensuring the normal operation of the insulator.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an adhesive for uniform silicone rubber / epoxy glass fiber interface electric field, characterized in that: The adhesive is a silane coupling agent grafted with a P-type AgAlO2 nanoparticle material; the silane coupling agent is a vinyl silane coupling agent and / or a methacrylate-based silane coupling agent; the P-type AgAlO2 nanoparticles are obtained by surface-modifying micron-sized Al(NO3)3·9H2O with AgNO3. The preparation method of the adhesive with uniform silicone rubber / epoxy glass fiber interface electric field comprises the following steps: (1) Dissolve aluminum in nitric acid, boil, remove impurities, evaporate and concentrate, cool, filter, wash and dry the precipitated crystals to obtain Al(NO3)3·9H2O; (2) dissolving the Al(NO3)3·9H2O and AgNO3 in water, adjusting the pH value of the solution to 13-14 with alkali, stirring, reacting, washing the obtained precipitate with ammonia water and nitric acid in turn until the pH value of the solution reaches neutral, rinsing with water, and drying to obtain P-type AgAlO2 nanoparticles; (3) mixing ethanol solution, isopropanol, methanol, acetic acid and concentrated nitric acid to obtain an adhesive solvent having a pH value of 4.5 to 3.5; (4) dispersing the P-type AgAlO2 nanoparticles, vinyl silane coupling agent and / or methacrylate silane coupling agent in an adhesive solvent in sequence, washing, filtering, and drying to obtain an adhesive; In step (2), the molar ratio of Al(NO3)3·9H2O to AgNO3 is 1:1-1.2; The concentration of the ethanol solution in step (3) is 78% by volume; the volume ratio of the ethanol solution, isopropanol, methanol, acetic acid and concentrated nitric acid is 100 mL: 4-6 mL: 4-6 mL: 4-6 mL: 4-6 mL; The amount of the P-type AgAlO2 nanoparticles, vinyl silane coupling agent and / or methacrylate silane coupling agent in step (4) is calculated according to the ratio of 1 g of P-type AgAlO2 nanoparticles to 10-15 mL of vinyl silane coupling agent and / or methacrylate silane coupling agent.

2. The method for preparing the adhesive for uniform silicone rubber / epoxy glass fiber interface electric field according to claim 1, characterized in that: The water used in the ethanol solution in step (3) is pure water with a conductivity of less than 2 μS / cm.

3. The method for preparing the adhesive for uniform silicone rubber / epoxy glass fiber interface electric field according to claim 1, characterized in that: Include at least one of the following: The concentration of nitric acid in step (1) is 20-80% by volume; The crystal filtration in step (1) is performed using filter paper with a pore size of 30-50 μm; The base in step (2) is NaOH; The concentration of the ammonia water in step (2) is 0.5-3 mol / L; The concentration of nitric acid in step (2) is 0.1-2 mol / L.

4. The method for preparing the adhesive for uniform silicone rubber / epoxy glass fiber interface electric field according to claim 1, characterized in that: Include at least one of the following: The temperature of the evaporation concentration in step (1) does not exceed 75°C; The washing in step (1) is performed with 0°C ice water; Step (4) The P-type AgAlO2 nanoparticles are dispersed by stirring for 10-15 minutes in a water bath at 40-60°C, and then ultrasonically treated for 10-15 minutes at a power of 60-120W; In step (4), the vinyl silane coupling agent and / or methacrylate silane coupling agent is dispersed by stirring in a water bath at 30-80° C. for 5-10 min.

5. The method for preparing the adhesive for uniform silicone rubber / epoxy glass fiber interface electric field according to claim 1, characterized in that: Include at least one of the following: The stirring time in step (2) is 1-8 hours; The reaction in step (2) is carried out at 150-250° C. for 20-80 hours.

6. An adhesive for uniform silicone rubber / epoxy glass fiber interface electric field prepared by the method for preparing an adhesive for uniform silicone rubber / epoxy glass fiber interface electric field as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Room temperature ammonia gas sensor using p-type delafossite structure oxide as sensitive material, and preparation method thereof

    CN108680609A